PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA PT. TRAKINDO UTAMA - -, Indra Andriade (EKONOMIA, 2015)
PT. Trakindo Utama is a company engaged in the procurement and leasing of heavy equipment. The company has been operating in Indonesia since the 1960s. The company has a large enough personnel. Every employee of PT. Trakindo Utama obliged to follow the Program of Education and Training to improve the quality of work. However, the growing number of similar companies entering into potential areas pemasarana PT. Trakindo Utama impact on the decline in sales. The decline in sales led to the loss of some of the facilities enjoyed by employees during this time, and of course psychologically will affect employee motivation and job satisfaction.The purpose of this research is: 1) Determine the influence of motivation and job satisfaction on the performance of employees of PT. Trakindo Utama. 2) Determine the influence of motivation on employee performance of PT. Trakindo Utama. 3) Determine the influence of job satisfaction on the performance of employees of PT. Trakindo Utama.The research was conducted at PT. Trakindo Utama located at Cipto Mangunkusumo street Samarinda .. The focus of research on motivation and job satisfaction on employee performance within a certain time period. Interviews with respondents conducted in April 2014. Selected samples of 85 respondents. Measurement data using primary data in the form of the result of filling the questionnaire by respondents. All the answers of the questionnaire qualitative converted into quantitative data to weigh the value of all answers using a Likert scale 1-5, with the assumption answer: Strongly disagree (1), Disagree (2), Neutral (3), Agree (4) and strongly agree (5). The collected data will be analyzed using Statistical Parametric test equipment by using multiple regression, in this case will be assisted by using SPSS version 20.00. (Statistical Program for Social Science). Results of the study are: 1) Motivation and job satisfaction have a significant effect tterhadap performance of employees of PT. Trakindo Utama. 2) Motivation does not significantly affect the performance of employees of PT. Trakindo Utama. 3) Job satisfaction significantly affect the performance of employees of PT. Trakindo Utama.